2016
DOI: 10.1039/c6ob00468g
|View full text |Cite
|
Sign up to set email alerts
|

Crowned spiropyran fluoroionophores with a carboxyl moiety for the selective detection of lithium ions

Abstract: The absorbance and fluorescence spectra of carboxylated spiropyrans containing methyl-1-aza-12-crown-4, methyl-1-aza-15-crown-5, methyl-1-aza-18-crown-6 moieties are compared in the presence of alkali metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Fluorescent sensors are excellent choices to image Li + in live cells or tissues, as they provide sensitive detection with high spatiotemporal resolution. Despite demonstrated success in using fluorescent sensors to detect divalent metal ions such as Ca 2+ , Zn 2+ , and Cu 2+ , , effective sensors for detecting monovalent metal ions, especially Li + , is quite limited. Among the fluorescent Li + sensors, sensors based on organic crown, such as chiral diaza-9-crown-3 derivatives, [2.1.1]-cryptates, KLI-1 and KLI-2, methyl-1-aza-12-crown-4, and 1-(9-anthryl)-4-ferrocenyl-2-aza-1,3-butadiene, have received the most attention. However, they have limited selectivity over other competing monovalent ions, such as Na + and K + , which are present in biological systems in much higher concentrations than that of Li + , and most of them have limited solubility in water and thus do not work well under physiological conditions. To our knowledge, Sabrina Heng lithium (SHL), based on merocyanine and spiropyran isomers changing upon Li + binding, was the first and is the only intracellular Li + optical sensor reported .…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent sensors are excellent choices to image Li + in live cells or tissues, as they provide sensitive detection with high spatiotemporal resolution. Despite demonstrated success in using fluorescent sensors to detect divalent metal ions such as Ca 2+ , Zn 2+ , and Cu 2+ , , effective sensors for detecting monovalent metal ions, especially Li + , is quite limited. Among the fluorescent Li + sensors, sensors based on organic crown, such as chiral diaza-9-crown-3 derivatives, [2.1.1]-cryptates, KLI-1 and KLI-2, methyl-1-aza-12-crown-4, and 1-(9-anthryl)-4-ferrocenyl-2-aza-1,3-butadiene, have received the most attention. However, they have limited selectivity over other competing monovalent ions, such as Na + and K + , which are present in biological systems in much higher concentrations than that of Li + , and most of them have limited solubility in water and thus do not work well under physiological conditions. To our knowledge, Sabrina Heng lithium (SHL), based on merocyanine and spiropyran isomers changing upon Li + binding, was the first and is the only intracellular Li + optical sensor reported .…”
Section: Introductionmentioning
confidence: 99%
“…Details on the synthesis of SHL are reported in the synthesis section of the Supplemental Information. In brief, the Li 1 sensor was prepared from 1-aza-15-crown-5 and 1-(2-hydroxyethyl)-2,3,3-trimethyl-3H-indol-1ium to give SHL with an overall yield of 20% using a modification to existing methodology (Heng et al, 2013;Stubing et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Abell combined the nitrophenol chromogenic moiety and crown ether receptor first reported by Pacey [ 24 ] and introduced a spiropyran group which cleaves to bind Li + in preference to other metal cations [ 48 , 49 ]. Investigation of chromoionophore 35 ( Scheme 15 ) showed that exposure to ultra-violet (UV) light at 365 nm in the presence of Li + generated increases in fluorescence which could be reversed with white light.…”
Section: Sensorsmentioning
confidence: 99%